PENGARUH PERFORMANCE EXPECTANCY, EFFORT EXPECTANCY, SOCIAL INFLUENCE, FACILITATING CONDITIONS, PERCEIVED RISK DAN ATTITUDE TERHADAP BEHAVIORAL INTENTION PENGGUNA DALAM ADOPSI APLIKASI SI D’NOK - Widyasari, Heni; Hanani, Retna (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
Population document services are a basic right of citizens. One of the efforts to fulfill it is by implementing the Si D'nOK Application. The Si D'nOK application was created to facilitate the management of administration and population documents in Semarang City. However, previous research shows that the implementation of the Si D'nOK Application has many obstacles. Theoretically, if there are still obstacles to the use of the Si D'nOK Application, then people's intention to use it will also be low. Based on this hypothesis, the purpose of this study is to analyze the factors that affect behavioral intention to use the Si D'nOK Application using the UMEGA model. There are seven variables analyzed, namely performance expectancy, social influence, perceived risk, and facilitating conditions as independent variables; effort expectancy and attitude as intervening 1 and 2, respectively; and behavioral intention to use as the dependent variable. This research uses a quantitative approach through a survey of 100 users of the Si D'nOK Application. Data analysis was performed with SmartPLS version 4.1.0.9. The results showed that performance expectancy have a positive effect on attitude by 14.7%; effort expectancy have a positive effect on attitude by 15.7%; social influence has a positive effect on attitude by 6.2%; perceived risk has a negative relationship and has no effect on attitude by 1%; facilitating conditions have a positive effect on effort expectancy and usage behavioral intention by 75.3% and 16.2%, respectively; and attitude have a positive effect on usage behavioral intention by 46.2%. There are suggestions that can be proposed, namely education and tutorials, complaint services, and directions to RT/RW to introduce the Si D'nOK Application.